ANXA11 mutations are associated with amyotrophic lateral sclerosis–frontotemporal dementia - Wang, Yu; Duan, Xiaohui; Zhou, Xiao; Wang, Renbin; Zhang, Xiangfei; Cao, Zhenhua; Wang, Xiaoxia; Zhou, Zhi; Sun, Yu; Peng, Dantao (Frontiers in Neurology, 2022)
Background The Annexin A11 (ANXA11) gene has been newly identified as a causative gene of amyotrophic lateral sclerosis (ALS) with or without frontotemporal dementia (FTD). The current study aimed to investigate the ANXA11 mutations in a Chinese ALS–FTD or FTD cohort. Methods We included ten probands/patients with suspected ALS–FTD or FTD. Mutational analysis of ANXA11 was performed through Next Generation Sequencing (NGS) and Sanger sequencing. We collected and reviewed clinical presentation, neuropsychology test results, brain-imaging findings, and electrophysiological examination findings. Results In total, six probands presented with ALS–FTD, and four with behavior variant FTD (bv-FTD). We identified a non-synonymous heterozygous mutation (c.119A>G, p.D40G) of ANXA11 in proband 1, which is associated with ALS. However, this is the first report of the mutation causing ALS–FTD. Proband 1 started with abnormal behavior and progressed to classic upper motor nervous disease. Magnetic resonance imaging (MRI) showed significant bilateral temporal lobe atrophy and bilateral hyperintensities along the corticospinal tracts.18F-AV45-PET imaging showed negative amyloid deposits. Conclusion ANXA11-related diseases have high clinical and genetic heterogeneity. Our study confirmed the contribution of ANXA11 mutations to ALS–FTD. The ANXA11 mutations established a complex genotype–phenotype correlation in ALS–FTD. Our research further elucidated the genetic mechanism of ALS–FTD and contributed to setting the foundation of future targeted therapy.